Reflexões sobre a importância da inserção de aulas experimentais em Química no município de Curuçá-PA - LIMA, Valéria Leal (2022)
This research aims to metamorphose the current educational context of high school chemistry teaching, in which the proposition that the student knows numerous formulas, memorize reactions and properties, but without relating them to the natural form that occur in nature, it is about applied nature and with a qualitative approach carried out in two State Schools in the Municipality of Curuçá-PA in order to demonstrate the importance and efficiency of working with experimental classes in chemistry and embracing this issue as one of the most plausible findings found as an educational proposal. In view of this, greater interaction of students in class was confirmed, questioning experiences and speculating on results.